Expression of SPARC during development of the chicken chorioallantoic membrane: evidence for regulated proteolysis in vivo. - Iruela-Arispe, M L (1995)
SPARC is a secreted glycoprotein that has been shown to disrupt focal adhesions and to regulate the proliferation of endothelial cells in vitro. Moreover, peptides resulting from the proteolysis of SPARC exhibit angiogenic activity. Here we describe the temporal synthesis, turnover, and angiogenic potential of SPARC in the chicken chorioallantoic membrane. Confocal immunofluorescence microscopy revealed specific expression of SPARC protein in endothelial cells, and significantly higher levels of SPARC were observed in smaller newly formed blood vessels in comparison to larger, developmentally older vessels. SPARC mRNA was detected at the earliest stages of chorioallantoic membrane morphogenesis and reached maximal levels at day 13 of embryonic development. Interestingly, steady-state levels of SPARC mRNA did not correlate directly with protein accumulation; moreover, the protein appeared to undergo limited degradation during days 10-15. Incubation of [125I]-SPARC with chorioallantoic membranes of different developmental ages confirmed that extracellular proteolysis occurred during days 9-15, but not at later stages (e.g., days 17-21). Comparison of peptides produced by incubation with chorioallantoic membranes with those generated by plasmin showed an identical pattern of proteolysis. Plasmin activity was present throughout development, and in situ zymography identified sites of plasminogen activator activity that corresponded to areas exhibiting high levels of SPARC expression. Synthetic peptides from a plasmin-sensitive region of SPARC, between amino acids 113-130, stimulated angiogenesis in the chorioallantoic membrane in a dose-dependent manner; in contrast, intact SPARC was inactive in similar assays. We have shown that SPARC is expressed in endothelial cells of newly formed blood vessels in a manner that is both temporally and spatially restricted. Between days 9 and 15 of chorioallantoic membrane development, the protein undergoes proteolytic cleavage that is mediated, in part, by plasmin. SPARC peptides released specifically by plasmin induce angiogenesis in vivo. We therefore propose that SPARC acts as an intrinsic regulator of angiogenesis in vivo.